Treadmill roller ski test predicts biathlon roller ski race results of elite U.S. biathlon women - Rundell, K. W. (Medicine & Science in Sports & Exercise, 1996)
This study evaluated ski-specific laboratory testing and the relationship of test parameters to biathlon race performance. Since the ski skating technique used exclusively during biathlon racing requires a large upper body contribution, treadmill roller ski test parameters may provide relevant information for ski-specific training and ski performance. Seven top U.S. female biathlon skiers performed lactate threshold and VO2 peak tests running (TR) and roller skiing (skating technique, RS) on a motor driven treadmill. In addition, a constant workload (14 km.h(-1), 6% grade) roller ski test to exhaustion at race pace (ET) on a motor driven treadmill, and a short-term double pole power test (DP) were also performed. Results indicate that lactate threshold VO2 and HR were significantly lower during RS than TR, DP power (w.kg(-1)) was related to RS VO2 peak (r = 0.90), but not to TR parameters. ET time to exhaustion was related to gross efficiency during ET (r = -0.86), RS VO2 peak (r = 0.80) and DP HR (% peak HR, r = 0.80). These results suggest that ski-specific laboratory testing provides better insight to ski performance than treadmill run testing.